Оперативний контроль обчислень на основі інформаційної надлишковості - Butsenko, Yu. P.; Savchenko, Yu. G. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
The problem of reliable control over industrial computer systems is considered. Generalization of the redundant variable method for any information processes with any hardware/software implementation is proposed.